1998
DOI: 10.1051/agro:19980801
|View full text |Cite
|
Sign up to set email alerts
|

Response of eight Cucumis melo cultivars to salinity during germination and early vegetative growth

Abstract: -In order to determine salt tolerance in eight varieties of Cucumis melo, two controlled environment experiments were carried out with seeds and seedlings. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 29 publications
2
28
0
3
Order By: Relevance
“…For all varieties, drought stress affected the germination and early seedling growth of rapeseed. This is may be due to alteration of enzymes and hormones found in the seed [28] or to the metabolic disorders induced by stress and generation of Reactive Oxygen Species [29]. It could also be a deficit of hydration of the seeds due to high osmotic potential causing inhibition of the mechanisms leading to the output of the radicle out of the coat and therefore a seed germination delay [30].…”
Section: Fig 4 Effect Of Peg Induced Drought Stress On Seedling Shomentioning
confidence: 99%
“…For all varieties, drought stress affected the germination and early seedling growth of rapeseed. This is may be due to alteration of enzymes and hormones found in the seed [28] or to the metabolic disorders induced by stress and generation of Reactive Oxygen Species [29]. It could also be a deficit of hydration of the seeds due to high osmotic potential causing inhibition of the mechanisms leading to the output of the radicle out of the coat and therefore a seed germination delay [30].…”
Section: Fig 4 Effect Of Peg Induced Drought Stress On Seedling Shomentioning
confidence: 99%
“…Salinity disturbs the mineral-nutrient relations in plants through their effects on nutrient availability, transport, and partitioning (Botía et al, 1998;Kaya et al, 2007;Cochard et al, 2010). Chlorophyll biosynthesis and nitrogen metabolism are also found to be affected due to high salinity (Ashraf, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The results of the present study showed that NaCl treatments caused an increase in Na + concentration and Na + /K + ; Na + /Ca 2+ ratios, and a decrease in K + and Ca 2+ concentrations of coriander shoot derived from both primed and non-primed seeds (Table 2). Previous studies showed similar effects of salinity in melon (Botia et al 1998) as well as in celery (Pardossi et al 1999), pepper (Chartzoulakis and Klapaki, 2000) and tomato (Romero et al 2001). However, seed priming induced avoidance of coriander shoot from toxic and nutrient deficiency effects of salinity on growth because of less Na + but more K + and especially Ca 2+ accumulation.…”
Section: Discussionmentioning
confidence: 53%